Zonation by ammonites and foraminifers of the Vraconnian-Turonian interval: A comparison of the Boreal and Tethyan domains (NW Europe / Central Tunisia) - Amédro Francis; Robaszynski Francis (Carnets de Géologie, 2008)
Since the end of the 19th century the interval comprising the uppermost Upper Albian, the Cenomamian, the Turonian and the basal Coniacian has been subdivided, first into ammonite zones, then, beginning in the middle of the 20th century, into zones of planktonic foraminifera. These two groups, one macrofossil, the other microfossil, are particularly effective for bio-chronostratigraphy thanks to their rapid rates of evolution. But differences in the faunal makeup between the Boreal domain (northwestern Europe) and the Tethyan domain (Mediterranean) have for a long time hindered precise correlation of the two domains. Today, in a time interval covering about 16 million years, there are 29 ammonite zones in the Tethyan domain versus 24 in the Boreal one, of which 16 are common to both domains. For the planktonic foraminifera the Tethyan domain has 11 zones, the Boreal domain 10, with 7 in common.